2022
DOI: 10.3389/fpsyt.2022.852712
|View full text |Cite
|
Sign up to set email alerts
|

Ability to Care for an Ill Loved One During the First COVID-19 Lockdown: Mediators of Informal Caregivers’ Stress in Europe

Abstract: Informal caregivers are overlooked, healthcare actors. They are at particular risk of distress and suffer from poor mental health. This study aimed to investigate the perceived stress and modulating factors during the first COVID-19 lockdown in Europe, regardless of the illness that care recipients suffer from. Sociodemographic data, coping resources, and perceived stress level using the Perceived Stress Scale (PSS-10) questionnaire were assessed using a web-based survey in Switzerland, France, and Belgium wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…This is further exacerbated by the stress associated with the potential risk of infecting and harming the individuals under their care [ 23 ]. Living with individuals who require care is linked to heightened perceived stress, primarily due to fears of illness and the potential disruption of daily activities [ 1 ]. In line with this, the present study has shown that residing with high-risk individuals serves as a predictor of COVID-19-related stress levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further exacerbated by the stress associated with the potential risk of infecting and harming the individuals under their care [ 23 ]. Living with individuals who require care is linked to heightened perceived stress, primarily due to fears of illness and the potential disruption of daily activities [ 1 ]. In line with this, the present study has shown that residing with high-risk individuals serves as a predictor of COVID-19-related stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…These caregiving-associated stressors may also give rise to familial and occupational difficulties, strain interpersonal relationships, and result in negative financial consequences [ 6 ]. Consequently, this creates a complex issue affecting both the caregivers and the well-being of the individuals under their care [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their coping strategies are related to their understanding of the situation and their available resources. Coping strategies are related to the environment, individual situations, and the ability to cope with stress in a specific situation, such as the coronavirus disease 2019 lockdown conditions ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Perceived stress, which refers to an individual's perceptions or ideas about the levels of stress they experience at a given time or during a specified period, can affect various aspects of the individual's life. 28 Previous studies have shown that perceived stress is a predetermined psychological state that occurs before experiencing depressive symptoms. 29,30 Individuals with high levels of perceived stress are often distressed; thus, they are likely to experience depressive symptoms.…”
Section: The Mediating Role Of Perceived Stressmentioning
confidence: 99%